The gender blindness of the education 5.0 framework: An obstruction to promotion opportunities for female academics in Zimbabwe - Muchabaiwa, Wonder; Chauraya, Efiritha (SAGE Publications, 2022)
This study explores the implications for the Education 5.0 framework on promotion opportunities for female academics in Zimbabwean universities. The framework emphasises research, lecturing, community service, innovation and industrialisation as job performance areas for a university lecturer. The qualitative research adopted a multi-case study design and purposively sampled 24 female lecturers from two universities in Zimbabwe. Data were collected through in-depth interviews, focus group discussions and analysis of official documents like staff-list records and research repositories. The study reveals that the expectations of the Education 5.0 framework are gender blind and tend to obstruct the promotion opportunities for female academics. Lack of funding in research activities, training in scientific writing, functional innovation hubs as well as the burden of domestic chores were the main obstacles to female academics’ promotion chances. The study recommends provision of research funds, training in scientific writing and establishing functional innovation hubs to fully operationalise the Education 5.0 framework.